Transmission Effectiveness of Resource Allocation Efficiency in Multitier Capital Market System. (6th August 2021) - Geng, Xiaoyuan
Abstract : With the continuous development of the capital market, in order to study the effectiveness of the multilevel capital market, the operation status of the multilevel capital market is used as the research object, and the Pareto analysis paradigm is used to study the effectiveness of the transmission mechanism of the resources allocation efficiency of the multilevel capital market. Research has shown that Pareto analysis model can be used to analyze the multilevel capital markets. Investors' irrationality and lack of professionalism further aggravate market volatility. Research on resource allocation of multilevel capital market systems and the effectiveness of the transmission mechanism has certain theoretical significance and practical value.